Beyond consequentialism - Hurley, Paul (Paul E.) (Oxford : Oxford University Press, 2009)
Hurley sets out a radical challenge to consequentialism, the theory which might seem to be the default option in contemporary moral philosophy. There is an unresolved tension within the theory: if consequentialists are right about the content of morality, then morality cannot have the rational authority that even they take it to have.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Consequentialism (Ethics); Pragmatism